2018
DOI: 10.3892/mmr.2018.9469
|View full text |Cite
|
Sign up to set email alerts
|

Two Paired Box 6 mutations identified in Chinese patients with classic congenital aniridia and cataract

Abstract: Congenital aniridia is a rare genetic disorder characterized by a variable degree of hypoplasia or absence of iris. It is frequently associated with keratopathy, cataract, juvenile-onset glaucoma and foveal and optic nerve hypoplasia. Mutations in the Paired Box 6 (PAX6) gene on chromosome 11p13 have been demonstrated to cause aniridia. The aim of the present study was to investigate the genetic variations of PAX6 in two sporadic patients from southern China with classic congenital aniridia and cataract. Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies 12,17, have identified several mutations in the CRYGC gene . Moreover, there have been previous reports 48,49 regarding frameshift mutations in CRYGC. However, we report the novel CRYGC frameshift mutation c.389_390insGCTG (p.C130fs) in exon 3,…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 12,17, have identified several mutations in the CRYGC gene . Moreover, there have been previous reports 48,49 regarding frameshift mutations in CRYGC. However, we report the novel CRYGC frameshift mutation c.389_390insGCTG (p.C130fs) in exon 3,…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mayer et al have shown that glaucoma has been identified in 52% out of 80 patients with congenital aniridia [187]. Lin et al have demonstrated that aniridia associated with glaucoma, congenital cataract, and lens subluxation may be caused by the recurrent nonsense mutation c.718C > T (p.Arg240X) in exon 9 of the PAX6 gene [188]. It has also been demonstrated that loss of PAX6 expression may cause an aniridia occurrence [189][190][191].…”
Section: Ntf4mentioning
confidence: 99%
“… 8 In addition to these seven genes, which have been widely reported and recognized as the causal genes for EL, there are also seven additional genes that have been reported to cause syndromes that include EL. ASPH is related to Traboulsi syndrome, 9 12 COL18A1 is related to Knobloch syndrome, 13 CPAMD8 is related to anterior segment dysgenesis, 14 PAX6 is related to aniridia, 15 VSX2 is related to microphthalmia, 16 TGFB2 is related to Loeys–Dietz syndrome, 17 and MTHFR is related to homocystinuria. 18 Variants in these genes with lens subluxation were reported sporadically.…”
mentioning
confidence: 99%